Effectiveness of an app-based intervention to improve well-being through cultivating positive thinking and positive emotions in an adult sample: study protocol for a randomized controlled trial - Uribe, Fabio Alexis Rincón; Favacho, Maria Fernanda Monteiro; Moura, Paula Marília Nascimento; Patiño, Diana Milena Cortés; da Silva Pedroso, Janari (Frontiers in Psychology, 2023)
Introduction Interventions to promote health and well-being based on the construction of psychological resources can positively impact daily life of users and foster human flourishing. Nowadays, mobile health represents a safe way to support health research and implement evidence-based psychological interventions. The present study aims to evaluate the effectiveness of a mobile app-based intervention program (OneUS) designed to cultivate positive emotions and positive thinking to improve overall well-being. Methods The study is designed as a randomized controlled trial. 200 participants will be randomly assigned to either a mobile health intervention condition (OneUS App) or an active control condition. The intervention consists of a program to cultivate positive emotions and positive thoughts. The active control intervention will comprise a set of mental imagery exercises and daily routine recording. The primary outcome comprises optimal well-being assessed using the multidimensional PERMA-Profiler scale. The sample will include adult people from the general population, who will be assessed at 8 time points: baseline (t1), intervention (t2, t3, t4, t5, t6) post-intervention (t7) and 3-month follow-up (t8). Discussion Mobile apps seem to be promising tools to promote health and well-being. This study will evaluate the effectiveness of a mobile app (OneUS) aiming to cultivate positive emotions and positive thinking to improve well-being. The main strength of this study is the development of an evidence-based mobile health app, based on intentional mental training, to promote well-being. The limitations of this study relate to potential participant drop-out and the non-generalizability of the results to clinical populations.